Exposure to hair metals and metal-mixtures associated with blood lipids and dyslipidemia in Chinese adults: Evidence from a national cross-sectional study - Yunjiang Yu; Wenjie Meng; Xiaohui Zhu; Zongrui Li; Tong Zheng; Ping He; Ying Yu; Chenyin Dong; Zhenchi Li; Hongxuan Kuang; Mingdeng Xiang; Xiaodi Qin; et al. (Ecotoxicology and Environmental Safety, 2025)
Background: Emerging evidence suggests that exposure to metals is associated with dyslipidemia; however, very little data is available on metal exposure in hair, and data regarding their joint and interactive effects for different metals on dyslipidemia are still sparse. Methods: Between 2020 and 2021, a cross-sectional study was conducted among 407 adults across eight provinces in China. Hair samples were analyzed for concentrations of 13 metals: arsenic (As), calcium (Ca), cadmium (Cd), chromium (Cr), copper (Cu), iron (Fe), magnesium (Mg), manganese (Mn), molybdenum (Mo), nickel (Ni), lead (Pb), selenium (Se), and zinc (Zn)—using inductively coupled plasma mass spectrometry (ICP-MS). Blood lipid biomarkers, including total cholesterol (CHOL), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C), were measured using an automated clinical chemistry analyzer. Multivariable linear and logistic regression models were used to examine associations between individual hair metal levels and lipid profiles or dyslipidemia status. Bayesian Kernel Machine Regression (BKMR) models were applied to assess the combined and interactive effects of metal mixtures on dyslipidemia. Results: We observed hair concentrations of Mo and Pb were positively associated with CHOL levels, while Ca and Cd were inversely associated with LDL-C. Hair Cd was also negatively associated with HDL-C. Logistic regression models showed that elevated Mo and Pb levels were significantly associated with higher odds of dyslipidemia [Mo: OR = 1.58, 95 % CI: 1.20–2.09; Pb: OR = 1.25, 95 % CI: 1.04–1.51] in single-metal models. In BKMR models, Mo and Pb showed the strongest and most consistent associations across exposure percentiles. The risk of dyslipidemia increased steadily with higher metal mixture exposure. Interactive analyses suggested a potential antagonistic effect between Cd and Pb, and a synergistic effect between Mo and Pb, where their joint exposures amplified the risk of dyslipidemia beyond their individual effects. Conclusion: This study revealed a positive association between hair metal mixtures, predominantly driven by Pb, and the risk of dyslipidemia, while also revealing an inverse Pb-Cd interaction effect on dyslipidemia.